2021
DOI: 10.1186/s13011-021-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of factors that influence opioid overdose prevention for justice-involved populations

Abstract: Background There is a high risk of death from opioid overdose following release from prison. Efforts to develop and implement overdose prevention programs for justice-involved populations have increased in recent years. An understanding of the gaps in knowledge on prevention interventions is needed to accelerate development, implementation, and dissemination of effective strategies. Methods A systematic search process identified 43 published papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 72 publications
(77 reference statements)
0
11
0
1
Order By: Relevance
“…A critical component for the reduction of post-release mortality from opioid overdose is linkage of individuals to community-based programs they are likely to use, such as drug treatment, harm reduction, or other health and social services (Zucker, Annucci, Stancliff, & Catania, 2015 ). Such programs can provide access points for naloxone distribution and ongoing prevention interventions (Grella et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A critical component for the reduction of post-release mortality from opioid overdose is linkage of individuals to community-based programs they are likely to use, such as drug treatment, harm reduction, or other health and social services (Zucker, Annucci, Stancliff, & Catania, 2015 ). Such programs can provide access points for naloxone distribution and ongoing prevention interventions (Grella et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protective factors to prevent pre-and post-treatment adverse effects of OUD, including overdose, best serve the treatment process when applied early. Individuals with criminal justice involvement need collaboration between criminal justice and community providers to access early treatment interventions to ameliorate the risk of overdose and death (Grella et al, 2021).…”
Section: Opioid Use Disordermentioning
confidence: 99%
“…According to Rudd et al (2016), the rate of deaths associated to opioid overdose, specifically prescribed opioids, have increased by 200% since 2000. In studies done by Binswanger, Blatchford, Mueller, and Stern (2013), Grella et al (2021) researchers found that overdoses were the leading cause of death of those that had been previously incarcerated. Prisons are ill equipped to address OUD as evidenced by lack of screening and treatment availability and given the physical dependency of OUD; incarceration rather than treatment does not support an efficacious solution.…”
Section: Court-mandated Treatment As a Successful Treatment Optionmentioning
confidence: 99%
“… 6 7 12 A scoping review between 2010 and 2020 found 43 publications relating to opioid overdose prevention in justice-involved populations (including correctional and community settings), of which 16 were cohort studies with data linkage. 13 The scoping review identified five core domains regarding opioid overdose prevention: acceptability, accessibility, effectiveness, feasibility and participant overdose risk. 13 The review found evidence of an immediate risk of overdose following release from prison; with the risk factors for opioid overdose including access to drugs, contact with drug using social groups and lack of social and socioeconomic support.…”
Section: Introductionmentioning
confidence: 99%
“… 13 The scoping review identified five core domains regarding opioid overdose prevention: acceptability, accessibility, effectiveness, feasibility and participant overdose risk. 13 The review found evidence of an immediate risk of overdose following release from prison; with the risk factors for opioid overdose including access to drugs, contact with drug using social groups and lack of social and socioeconomic support. 13 Often, this at-risk group had contact with community-based service providers (after their release and before overdose) thereby pointing to opportunities for overdose prevention interventions during this period.…”
Section: Introductionmentioning
confidence: 99%